IMPACT OF LOAD DISTRIBUTION ON ENERGY GENERATION IN A PIEZOELECTRIC FLOOR PROTOTYPE (Journal of Renewable Energy and Mechanics, 2025)
The increasing global demand for energy has intensified the search for sustainable and environmentally friendly alternatives, one of which involves harvesting mechanical energy from human activities using piezoelectric materials. This study designed and evaluated a piezoelectric floor prototype consisting of 128 parallel-connected PZT elements supported by spring columns as force transmission media, employing a Research and Development (R&D) approach. Experimental tests were conducted under two loading patterns (walking across and jumping) with mass variations of 69kg and 98kg, each repeated ten times. The output signals were recorded using an oscilloscope in a closed-circuit configuration with a 1 Ω resistor as the load. Results indicate that the jumping pattern produced higher voltage and current compared to walking, while increased body mass significantly enhanced system performance. Overall, the generated voltage ranged from 1.5 to 8.9V with an average current up to 11.7mA, where jumping with the heavier mass yielded the highest output. These findings confirm that both mass variation and loading pattern directly affect energy performance and highlight the potential of piezoelectric technology to contribute to sustainable energy development. Further studies are required to improve signal stability and to integrate the system with energy storage devices, thereby supporting practical large-scale applications.